Integrasi Simulasi Virtual Reality (VR) Imersif Terhadap Pemahaman Konsep Pengukuran Siswa Sekolah Dasar - Erni Nurjanah; Yoesrina Novia Vini Syafitri; Siti Aisyah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
This study aims to examine the effect of integrating immersive Virtual Reality (VR) simulations on elementary school students' understanding of measurement concepts. The primary issue addressed is the low level of student comprehension regarding abstract measurement concepts, which are often difficult to visualize through conventional teaching methods. This research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of two fourth-grade classes at SD Negeri 1 Selaawi: the experimental class received VR-based learning, while the control class underwent traditional instruction. The research instruments included a conceptual understanding test, a student response questionnaire, and classroom observation. Data analysis was conducted using normality tests, the Mann-Whitney U test, and descriptive statistics. The results revealed a significant improvement in students' understanding of measurement concepts in the experimental class compared to the control group. The average posttest score in the experimental class increased from 70.58 to 75.24, while the control class rose from 72.28 to 73.71. The Mann-Whitney U test showed a significance value of 0.009 for the posttest, indicating a statistically significant difference between the two groups. Moreover, the questionnaire results indicated positive student responses to VR-based learning, especially in terms of visualization and conceptual comprehension. The use of VR simulations proved effective in providing a more interactive, contextual, and enjoyable learning experience. Therefore, the integration of VR technology is recommended as an innovative strategy in mathematics instruction at the elementary level, particularly to enhance students’ conceptual understanding of measurement.